2016
DOI: 10.1155/2016/5823013
|View full text |Cite
|
Sign up to set email alerts
|

Broad Spectrum Anti-Quorum Sensing Activity of Tannin-Rich Crude Extracts of Indian Medicinal Plants

Abstract: Quorum sensing (QS) mechanisms have been demonstrated to have significance in expression of pathogenicity in infectious bacteria. In Gram negative bacteria the autoinducer molecules that mediate QS are acyl homoserine lactones (AHL) and in Gram positive bacteria they are peptides called autoinducing peptides (AIP). A screening of tannin-rich medicinal plants was attempted to identify extracts that could interrupt the QS mechanisms in both Gram positive and Gram negative bacteria over a wide range of concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…All the extracts showed distinct protein binding ability and may be disrupting QS either by inactivating enzymes responsible for the synthesis of the AIs or by binding to protein receptors of QS signals. [ 73 ]…”
Section: P Lant B Y-products As mentioning
confidence: 99%
“…All the extracts showed distinct protein binding ability and may be disrupting QS either by inactivating enzymes responsible for the synthesis of the AIs or by binding to protein receptors of QS signals. [ 73 ]…”
Section: P Lant B Y-products As mentioning
confidence: 99%
“…Extracts from Korean indigenous plants also exhibited QSI against C. violaceum and P. aeruginosa bioreporters [166]. Recently, Shukla and coworkers [186] found that tannin-rich crude extracts from six Indian medicinal plants ( Phyllanthus emblica , Terminalia bellirica , Terminalia chebula , P. granatum , Syzygium cumini , and Mangifera indica ) commonly used in Ayurveda showed QQ properties against C. violaceum and S. aureus at sub-inhibitory concentrations. Anti-QS activity was also obtained against S. aureus with methanolic extracts rich in pentacyclic triterpenes (ursene and oleanene derivatives) from the Italian medicinal plant Castanea sativa .…”
Section: Plant-based Strategies To Deal With Unwanted Biofilmsmentioning
confidence: 99%
“…Further, transcriptional analysis showed that this fraction downregulates the expression of curli genes ( csgB and csgD ) and various motility genes ( fimA, fimH, flhD, motB, qseB , and qseC ) in Escherichia coli . Broad spectrum anti-QS activity of hydrolysable tannin-rich extracts of Indian medicinal plants Phyllanthus emblica, Terminalia bellirica, Terminalia chebula, Punica granatum, Syzygium cumini and Mangifera indica was reported by Shukla and Bhathena [96]. The authors suggest the tannin bioactivity mechanism is mediated by protein precipitation that may disrupt QS by inactivating various enzymes responsible for the autoinducer synthesis or by binding to protein receptors of QS signals.…”
Section: Plant-derived Molecules That Affect Ahl-mediated Qs In Bamentioning
confidence: 98%